Efficacy of digital radiographic systems in the quality assessment of intracanal materials used for primary teeth - Guilherme Fantini Ferreira; Larissa Pereira Lagos de Melo; Mariana Rocha Nadaes; Fernanda Maria Mazoni Reis; Fernanda Miori Pascon; Deborah Queiroz Freitas (Universidade Estadual de Campinas, 2019)
Aim: To evaluate the performance of three digital radiographic systems in the analysis of root canal filling quality using different intracanal materials for primary teeth. Methods: Twenty-five bovine teeth were divided into 5 groups: Calen® combined with iodoform; Calen® combined with zinc oxide; zinc oxide and eugenol; UltraCal®XS, and 2% chlorhexidine combined with Ca(OH)2 + zinc oxide. Periapical radiographs were obtained with the VistaScan, Express, and SnapShot systems. The quality of the images was evaluated objectively (radiopacity) and subjectively (apical sealing and filling homogeneity). As the reference standard, the teeth were scanned with a micro-CT device. Results: Radiopacity differed among the radiographic systems and materials tested. In general, the greatest difference was observed between the Express and VistaScan systems; Calen® combined with iodoform resulted in the highest radiopacity. The radiographic systems did not differ in terms of homogeneity. However, Calen® combined with iodoform differed from the other materials and exhibited the best results. Regarding apical sealing, the SnapShot system and Calen® combined with zinc oxide provided the best results. Conclusion: Direct digital systems show better performance in evaluating the quality of endodontic treatment in primary teeth and should be preferred for this purpose.